2017
DOI: 10.1590/1809-4430-eng.agric.v37n6p1081-1090/2017
|View full text |Cite
|
Sign up to set email alerts
|

Biogas Production From Dairy Cattle Manure, Under Organic and Conventional Production Systems

Abstract: ABSTRACT:The purpose of this study was to evaluate the production of biogas, as well as the biogas production potential resulting from the anaerobic biodigestion of dairy cattle manure under organic (CMOS) and conventional (CMCS) production system. Also, the concentration of thermotolerant coliforms was evaluated after the biodigestion process. Therefore, bench biodigesters prototypes were supplied with CMOS and CMCS for 30 weeks. The experimental design was completely randomized with four repetitions for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 14 publications
3
14
1
7
Order By: Relevance
“…Bench-top Indian model biodigesters, consisting of a "water seal" containment chamber, fermentation chamber, gasometer, and U-bulb manometer with water as a manometric liquid, as described by Matos et al (2017a), were used in the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Bench-top Indian model biodigesters, consisting of a "water seal" containment chamber, fermentation chamber, gasometer, and U-bulb manometer with water as a manometric liquid, as described by Matos et al (2017a), were used in the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Pode-se substituir o nitrogênio mineral por orgânico suínos líquidos, conforme dosagens recomendadas em culturas específicas a exemplo do milheto ou milho safrinha (Castagnaraet al, 2009). Quando ainda não decompostos, os t al., 2014) em comparação com bovinos (Matos et al, 2017) e aves, possuem quantidades intermediárias de N (1,8-2,5%), P (1,2-2,0%) e K (0,8 Aplicações inovadoras do biogás incluem obtenção de H2 via reforma catalítica que pode ser a combustível (Schaffer et al, 2014). Este artigo tem como objetivo analisar a evolução temporal da disponibilidade de biogás e potencial energético, e respectiva distribuição espacial do rebanho suíno no estado de Mato Grosso do Sul; municípios, micro e mesorregiões geográficas.…”
Section: Quantificação Do Biogás E Matériaunclassified
“…A microrregião "Dourados" (destacada na Fig. 1A (Matos et al, 2017) e aves, 2,0%) e K (0,8-1,5%). Aplicações inovadoras do biogás incluem obtenção de H2 via reforma catalítica que pode ser Este artigo tem como objetivo analisar a evolução temporal da disponibilidade de biogás e potencial energético, e respectiva distribuição espacial do rebanho suíno no estado de mesorregiões geográficas.…”
Section: Quantificação Do Biogás E Matériaunclassified
See 1 more Smart Citation
“…Comparing organic and conventional management in dairy farms, Matos et al [66] observed higher biogas yield from cow manure produced by dairy herds under the conventional production system compared to AD with cow manure under the organic production system. These differences in methane yield may be due to the different diet fed to the animals, as in the conventional management diets are based on concentrate that provided more appropriate substrates for the AD process than organic diets, mainly based on roughage.…”
Section: Livestock Manurementioning
confidence: 99%